The Public's Interest in the Production of Tongbara Chili Sauce inKedonganan Village, Bali - Sipakkar, Reynhard Jopinus; Ary Pradana, Yoshua; Pradnya Paramita, Kadek; Ayu Hanifa, Adinda; Putu Wiweka Krisna Dewi, Ayu (Journal Of Artha Biological Engineering, 2024)
Kedonganan Beach, located in Kuta District, is one of Bali's coastal areas with significant marine resource potential. Most of the local population works as fishermen due to the village's location, bordered by the sea on both the west and east sides. This makes the majority of its residents engaged in the fisheries and marine sectors, including as fishers. One of the fish species with high potential, and a primary catch for fishermen in the Kedonganan area, is tuna. The method used in this study involvedcollecting data through questionnaires distributed via Google Forms for greater efficiency. The goal of this research is to develop the "Tongkol Membara" (Spicy Tuna) product into a micro, small, and medium enterprise (MSME). This requires public interest, especially from the fisherwomen, in the production of this product. The results from seven respondents indicated a 85.7% interest in developing the tuna chili sauce business. Most also expressed interest in participating in a series of activities and continuing the "Tongkol Membara" business. However, 28.5% of respondents were not interested in forming new groups for fisherwomen (BuLayan) because they already belong to existing fisher groups in their respective communities.